2019
DOI: 10.21037/jtd.2019.01.30
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent imaging using indocyanine green during esophagectomy to prevent surgical morbidity: a systematic review and meta-analysis

Abstract: Background: Fluorescent imaging using indocyanine green (ICG) is an emerging technique that aids the surgeon with intraoperative decision making during upper gastrointestinal cancer surgery. In this systematic review we aim to provide an overview of current practice of fluorescence imaging using ICG during esophagectomy, and to show how this technology can prevent surgical morbidity, such as anastomotic leakage, graft necrosis and chylothorax. Methods: The PRISMA standard for systematic reviews was used. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 35 publications
0
56
0
1
Order By: Relevance
“…It has also been reported that ICG fluorescence was used to assess blood flow at the colonic anastomosis to reduce the suture failure rate [17,18]. In esophagectomy, ICG fluorescence has been used to assess gastric conduit blood flow [19][20][21][22]. In the present case, there was no visual evidence of poor blood flow in the rest of the stomach but there was a possibility of poor blood flow near the tip of the remnant stomach due to poor blood flow network in the gastric wall.…”
Section: Discussionmentioning
confidence: 51%
“…It has also been reported that ICG fluorescence was used to assess blood flow at the colonic anastomosis to reduce the suture failure rate [17,18]. In esophagectomy, ICG fluorescence has been used to assess gastric conduit blood flow [19][20][21][22]. In the present case, there was no visual evidence of poor blood flow in the rest of the stomach but there was a possibility of poor blood flow near the tip of the remnant stomach due to poor blood flow network in the gastric wall.…”
Section: Discussionmentioning
confidence: 51%
“…However, anastomotic leakages are associated with postoperative mortality, reoperations, prolonged hospital and critical care unit stay, delayed or non-administration of adjuvant therapy, and stricture formation that may require subsequent endoscopic or surgical treatment [ [9] , [10] , [11] , [12] , [13] ]. There are several patient, disease, and technical factors that contribute to anastomotic leakage but adequacy of perfusion at the anastomotic site, a surgically modifiable factor, is considered one of the most crucial [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Discussionmentioning
confidence: 99%
“…Complete washout of the ICG occurs within 20 min of injection [ 23 ]. The technology is informative, easy to use, and not linked to any major complication [ 14 , 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AL after esophagectomy is a severe postoperative complication with potential poor prognosis. In recent years, a wide range of measures to prevent AL has been suggested, including improvement in anastomotic techniques [15][16][17] and gastric tube formation [18,19] , utilization of pedicled omental aps [20,21] or mobilized pleura [22] , avoiding excessive tension at the anastomosis [23] , intraoperative perfusion monitor [24,25] , e cient gastric decompression [26] , and meticulous perioperative management. Nevertheless, among them, only few interventions are supported by strong clinical evidence, and then anastomotic leakage has still been an important postoperative complication.…”
Section: Discussionmentioning
confidence: 99%